PEMANFAATAN KOLOLEKSI REFERENSI UPT PERPUSTAKAAN DALAM MENUNJANG PROSES BELAJAR MAHASISWA POLITEKNIK NEGERI MANADO - Alfons, Lussy (ACTA DIURNA KOMUNIKASI, 2014)
Abstract: Utilization Unit Library Reference Collection in Manado State Polytechnic students Introduction: The college is an institution of higher education, which run sequentially and planned where there is a process of the scientific community in there. In Law on the National Education System 20 in 2003, stated that each unit of formal and non-formal education provides the infrastructure and facilities that meet the needs of education in accordance with the growth and development of the potential physical, intellectual, social, emotional and mental high sense. Education participants as an ideal vehicle to create a community of learning needs to be library as an element supporting the achievement of the college. It would be better for the higher education institutions can make the library service points in this case is called the referens.Development library services will appear on the components of collections, services, building or room, equipment and so forth. competency library collection particularly interesting to study, because it is through the collection of students expected to be able to develop insight by utilizing the library as a library user study. Is a major factor in the activities of reference services. Reference collection consists of various types such as dictionaries, encyclopedias, thesis, scientific papers, teaching materials, teaching materials, research reports, final reports, dissertations, journals and magazines. This collection is used by the students to the needs of basic information such as the meaning of a term, a description of an understanding, as well as the address of the person or agency specific statistical data. Methods: The method used in this study is the method kualitatif. Results : There are 12 informants in this study at Polytechnic Library Unit Manado.Suggestion: It is expected that the existence of a reference collection at the Polytechnic Library Unit Manado can be utilized by the students, not just when there is a settlement thesis given by lecturer. Keywords: Utilization collection, learning process, students. Abstrak: Pemanfaatan Koleksi Referensi UPT Perpustakan dalam Mahsiswa Politeknik Negeri Manado Pendahuluan: Perguruan tinggi adalah lembaga pendidikan tinggi, yang berjalan secara berurutan dan terencana dimana terdapat suatu proses kegiatan dengan masyarakat ilmiah didalamnya.Dalam Undang-Undang Sistem Pendidikan Nasional No. 20 tahun 2003 disebutkan bahwa setiap satuan pendidikan formal dan non formal menyediakan sarana dan prasarana yang memenuhi keperluan pendidikan sesuai dengan pertumbuhan dan perkembangan potensi fisik, kecerdasan intelektual, sosial, emosional dan kejiwaan peserta didik.Perguruan tinggi sebagai wahana ideal untuk menciptakan masyarakat belajar perlu adanya perpustakaan sebagai suatu unsur penunjang tercapainya tujuan perguruan tinggi. Akan lebih baik bagi lembaga pendidikan tinggi tersebut dapat membuat titik-titik layanan perpustakaan dalam hal ini disebut dengan layanan referens.Perkembangan perpustakaan akan tampak pada komponen-komponen koleksi, pelayanan, gedung atau ruangan, perlengkapan dan lain sebagainya. kompotensi perpustakaan khususnya koleksi menarik untuk dikaji, karena melalui koleksi mahasiswa diharapkan mampu untuk mengembangkan wawasanya dengan memanfaatkan perpustakan sebagai tempat belajarnya.Kemudian Pengguna perpustakaan adalah faktor utama dalam kegiatan jasa referensi. Koleksi referensi terdiri dari berbagai jenis seperti kamus, ensiklopedi, tesis, karya ilmiah, bahan ajar, bahan ajar, laporan penelitian, laporan akhir, disertasi, jurnal dan juga majalah. koleksi ini digunakan oleh mahasiswa untuk kebutuhan informasi dasar seperti arti sebuah istilah, uraian suatu pengertian, alamat orang atau instansi serta data statistik tertentu. Metode: Metode yang digunakan dalam penelitian ini adalah metode kualitatif.Hasil: Terdapat 12 informan dalam penelitian ini di UPT Perpustakaan Politeknik Negeri Manado.Saran: Diharapkan agar keberadaan koleksi referens di UPT Perpustakaan Politeknik Manado dapat di manfaatkan oleh mahasiswa,bukan hanya ketika ada penyelesaian tugas akhir yang diberikan oleh dosen. Kata kunci: Pemanfatan koleksi,Proses belajar,Mahasiswa.